2009
DOI: 10.1007/s11355-009-0067-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an urban park on air temperature differences in a central business district area

Abstract: Urban open spaces such as parks can act as urban cool islands. For example, in Seoul, Korea, the many Lee Dynasty royal palaces and tombs act as urban cool islands that reduce the temperature of the park compared with the surrounding urban areas. In order to determine the effect of air temperature differences because of the urban royal tomb park, Seolleung Royal Tomb Park (SPK) and the nearby Seolleung subway station (SLS), air temperatures were recorded at 10 min intervals from November 9th, 2007 to November … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(38 citation statements)
references
References 11 publications
2
35
0
1
Order By: Relevance
“…Yokobori and Ohta (2009), Lee et al (2009) and Bowler et al (2010) also showed that the influence of vegetation on air temperature was bigger during the night. None of them refer to cooling by evapotranspiration.…”
Section: Phase 1 -Site-dependent Coolingmentioning
confidence: 91%
“…Yokobori and Ohta (2009), Lee et al (2009) and Bowler et al (2010) also showed that the influence of vegetation on air temperature was bigger during the night. None of them refer to cooling by evapotranspiration.…”
Section: Phase 1 -Site-dependent Coolingmentioning
confidence: 91%
“…The widespread urban sealing affects the natural climate functions of soils by diminishing the amount of water that infiltrates and by increasing run-off. Even more, sealing obstructs the exchange between soil and atmosphere [111][112][113], so a local air temperature reduction function of soils by evapotranspiration is no longer given. Apart from this urban characteristic, a study regarding the local impact of groundwater table depth on urban air temperature [25] suggests that local topsoil moisture can be regarded as one significant impacting factor for the daytime increase of air temperature.…”
Section: Humidity and Evapotranspirationmentioning
confidence: 99%
“…Several studies focus on air temperatures reducing urban parks and unsealed vegetated areas and their relevance for nearby surroundings [111,112,[114][115][116][117][118][119]. Nevertheless, the climate influencing efficiency of urban soils and vegetation is coupled.…”
Section: Humidity and Evapotranspirationmentioning
confidence: 99%
“…Greener cities are cooler cities, and several researchers have attempted to quantify the cooling effect of greenery [69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84]. The temperature difference between the parks and their urban surroundings seems to depend on the size of the parks [71,75,[85][86][87][88][89] and on the design of the park [78,90].…”
Section: Greenery Standardsmentioning
confidence: 99%